Incidence of musculoskeletal injuries in professional dancers - Brooker, Heather (University of Cape Town, 2020)
Background: Professional ballet dancers focus on the high levels of discipline, perfection and mobility to achieve the fluid, controlled lines of movement presented on the stage. Dancers undergo long hours of strenuous, repetitive training which increases the risk of developing overuse or traumatic injuries and may compromise the longevity of dancers' careers. Relevant research, particularly in the South African context, is needed to provide recommendations on the intrinsic and extrinsic factors contributing to musculoskeletal injuries in professional ballet dancers. Aim: The aim of this study was to determine the incidence of musculoskeletal injuries and their associated risk factors over a three-month period in adult female professional ballet dancers in South Africa. Specific Objectives: The specific objectives of this study were: • To determine the incidence of traumatic and overuse injuries per 1000 dance hours over a three-month training and performance period in South African female professional ballet dancers; • To determine the relationships between a) Functional Lower Extremity Evaluation (FLEE) scores and injury incidence; b) intrinsic factors (amenorrhoea; body mass index; skinfold measurements; caloric intake) and injury incidence; and c) extrinsic factors (training hours; performance hours) and injury incidence respectively, in South African female professional ballet dancers. Methods: This study had a prospective, descriptive design. Eighteen female dancers were recruited from professional dance companies in the Gauteng, Western Cape and North West provinces of South Africa. Data were collected over a three-month period and included a subjective questionnaire, three-day food diary, skinfold measurements and the Functional Lower Extremity Evaluation (FLEE). Injuries were reported using an injury reporting form over the three-month period. Results: Participants had an average age of 22.1 ± 3.0 years. The dancers had an average BMI of 21.4 ± 2.1 kg.m⁻²; LBM of 41.7 ± 4.9 kg and body fat percentage of 24.7% ± 2.9%. Injury incidence was 3.3 injuries per 1000 dance hours with a total of 4605.58 hours reported overall. Of the 15 injuries reported, 13 occurred in the lower limb, with eight in the ankle and foot. Overuse injuries accounted for 93.3% of the total injuries, with only one traumatic injury reported. None of the descriptive characteristics was associated with increased injury risk. The average caloric intake of 1810.0 ± 503.7 calories, while lower than what is recommended for female athletes, also showed no significant relationship to injury. There were also no significant associations between pre-injury FLEE measurements and training loads; and injury incidence over the course of the study. Conclusion: An overall injury incidence of 3.3 injuries per 1000 dance hours was found in professional female ballet dancers in South Africa, which is higher than the injury incidences identified in previous studies in high-income countries. With regards to injury profile, overuse injuries are 86% more prevalent than traumatic injuries among this population type. We were unable to identify any intrinsic or extrinsic risk factors associated with injury incidence; however, we recognise the limitations of the small sample size in this study. With a high level of injury incidence and inconclusive results on injury risk factors, there is a clear need for significant further research in the field of injury prevention in professional ballet dancing. Further, this study identified a strong need for further research in South African dance companies to facilitate injury prevention and management in South Africa.